STUDY ON THE EFFECTS OF DIFFERENT PACKAGING MATERIALS USED ON THE QUALITY OF CATFISH MEATBALLS DURING STORAGE AT ROOM TEMPERATURE - Daniel Sianipar; Syahrul '; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the effect of various types of packaging materials on the quality of catfish meatballs those various color during storage at room temperature. The research method used was experimental method that was processing the various colors of catfish meatballs and then packing them by using different types of packaging materials during storage at room temperature for 0 day, 15 days and 30 days. Types of packaging materials used were HDPE and Aluminum foil with HDPE lining. The parameter measured were the value of the organoleptic appearance, aroma, texture and flavor, the proximate water content, fat content, the value of TBA, and total bacterial colonies. The results showed that the best packaging material used was HDPE plastic to protect the product during storage for 30 days. The product was showing the value of consistence 7.46, odor 7.34, texture 7.20, and flavor 7.53. Whilst the moisture content was 4.52%. The value fatty acid content 7,10 with using HDPE with aluminum (K0) packaging and the value TBA 0,68 with using HDPE (H0) packaging. Keywords: Aluminium foil, catfish, HDPE and meatball